Disposal of infective waste: demonstrated information and actions taken by nursing and medical students - Adenícia Custodia Silva Souza; Sergiane Bisinoto Alves; Mary Rocha Carneiro Garcia Zapata; Anaclara Ferreira Veiga Tipple; Larissa Oliveira Rocha; Janaína Valadares Guimarães; Milca Severino Pereira (Universidade Federal de Goias, 2015)
The inappropriate disposal of infectious waste generates occupational and environmental risks, representing the main cause of accidents with biological material. The aim of the present study was to verify the knowledge and the practice regarding the disposal of infectious waste among nursing and medical undergraduate students at a public university in the state of Goiás. Data were collected with the application of a questionnaire. The respondent students were observed in their practice and data were recorded in a checklist. Nursing students presented greater knowledge than medical students on the disposal of contaminated gloves (x²; p<0.001), as well as on the disposal of sharp cutting instruments (p=0.001). Contaminated gloves were disposed of into bags for common waste both by the nursing and the medical students. Results evidenced that the knowledge of students on the disposal of infectious waste was poor and insufficient to ensure its application to practice.